Kehadiran Subkultur Klub Motor di Ruang Publik Kota Bandung - Nurhijrah, Nurhijrah (RUAS, 2019)
The presence of subcultures in urban society is as a result of the heterogeneity of culture. One of subculture that presence in Bandung city is a motorcycle club which can be found in almost every corner of the Bandung city, especially in public spaces. This study was conducted to identify the phenomenon of the process of motorcycle club subculture occupy space in public open space under flyover in Bandung city. Data was collected by observation and interview members of the subculture as a subject of the research. The result showed that the main motive for using public open space under flyover is the desire for self-existence that cannot be accommodated in public space that already exists. Utilization of the space under flyover by the motorcycle club gives new meaning to the space that originally did not have a function in urban spatial. However they also do legitimacy of power over space by said that â€œthe space is theirsâ€. Therefore architects and planners should consider subculture as a part of the society that have the same right to access public open space and do their activities in Bandung City.Â